Essentials of business communication - Guffey, Mary Ellen (Cengage, 2023)
Ensure you have the job-ready writing and communication skills that today's employers demand with Guffey/Loewy's ESSENTIALS OF BUSINESS COMMUNICATION, 12E. This market-leading text and its online study tools help you develop the professional and communication skills that employers seek, including writing, speaking, critical thinking and teamwork. Updated employment chapters offer insights into a labor market that is more competitive and dependent on technology than ever before. The latest trends, technologies and practices, based on interviews with practitioners and the research of thousands of articles and blogs emphasize transferable professional skills. Timely advice guides you through building your brand, searching for a job, writing a winning resume, interviewing effectively and using LinkedIn. Optional editing challenges and grammar reviews and a complete grammar guide at the end of the book help you improve critical language skills.